Distribution and Area of Lebak Marsh Based on Hydrotopographic Characteristics in Grogol Subdistrict, Sukoharjo Regency - Jwalita, Aliendina; Renata Ade Yudono, Andi; Asrifah, Rr. Dina (Journal of World Science, 2023)
This research aims to determine the distribution and extent of leaky swamps based on hydrotopographic characteristics. The method used is an empirical approach using the Thornthwaite Mather water balance. The research data comes from both primary and secondary sources. Primary data collection involves field observations, measurements, and mapping, which provide data on soil texture, vegetation, fauna, topography, and aerial photos. Secondary data is obtained from institutions/agencies. Soil texture data is obtained through purposive random sampling. The extent of the leaky swamp is +104,252 m2, and it can hold a maximum volume of +116,028.25 m3 of water. The research results indicate the presence of two types of leaky swamps based on their hydrotopographic characteristics: shallow swamps and deep swamps. Shallow swamps are located on the riverbanks with higher elevations, covering an area of 30,462.54 m2. Meanwhile, deep swamps are situated in the center of the swamp with lower elevations in the form of basins, covering an area of 37,733.08 m2. This research has implications for a better understanding of Lebak swamps in the Grogol District. The findings can be used to develop more effective water resource management strategies. Furthermore, this research can serve as a foundation for further in-depth studies, such as ecological studies of swamps, research on water quality, or analyses of the impact of climate change on hydrotopography and the distribution of Lebak swamps.